Immunogenicity of recombinant Mycobacterium smegmatis expressing antigen 85b epitopes as a potential tuberculosis vaccine candidate - Nur Ayuni Kadir (2017)
Tuberculosis (TB) remains a major worldwide health problem which causes more than 1.3 million deaths annually. The development of a new vaccine as a replacement of Bacille Calmette Guerin (BCG) or to improve its efficacy is one of the goals mooted by the World Health Organization (WHO) to control TB. Mycobacterium smegmatis (M smegmatis) is nonpathogenic and commensal in humans, which shares many characteristics with Mycobacterium tuberculosis (M tuberculosis). Mycobacterial vectors including M smegmatis have been successfully used in the development of experimental vaccines against TB. In the current study, recombinant M smegmatis expressing selected Ag85B epitopes (PI, P2 and P3) was constructed (rMs064). The immunomodulatory effects of rMs064 were evaluated in J774A.I murine macrophage cells. Our results demonstrated the capacity of rMs064 to induce the expression of the macrophage activation markers; MHC class nand CD40 molecules, and the production of IL-6, IL-IO and IL-12p70 cytokines. Both rMs064 and M smegmatis transformed with the empty plasmid (rMsOI2 as a control) were capable to induce phagocytic and mycobactericidal activity in macrophages as well as the production of IL-l ~ and TNF -(1 cytokines. In addition, J774A.l macrophages infected with both rMs064 and rMs012 also increased the expression of inducible nitric oxide synthase (iNOS) and the production of nitric oxide (NO), which are crucial mediators of anti-mycobacterial activity. The induction of autophagy as quantified by LC3B-II detection in rMs064 infected macrophages showed inconclusive results in our experimental conditions. The capacity of rMs064 to induce specific cellular and humoral immune response in Balb/C mice against the expressed epitopes was evaluated. The proliferative responses of splenocyte from rMs064-immunized mice stimulated with P2 and P3 epitopes showed significant increase as compared to control groups. Cytokine production by plenocytes up n stimulation with Ag85B epitopes and serum specific IgG and its ubclasses were determined. The re ults showed significant production of IL-12p70 and IL-23 when splenocytes were stimulated with PI, P2 and P3 epitopes in mice immunized with rMs064. In addition, significant IFN-y production was found in splenocytes of rMs064-immunized mice when stimulated only with PI epitope. For the evaluation of the T cell activation by rMs064, mice were immunized with rMs064, rMsO 12, PBS and KLH-85B. Macrophages infected with rMs064 and co-cultured with KLH- 85B sensitized splenocytes induced significant production of IF -y and TNF-a.. The specific total IgG and IgG 1 subclass showed significant increase again t all three Ag85B epitopes on rMs064-immunized mice as compared to controls. rMs064 immunized mice showed significant increase of IgG2a and IgG2b only against P2 epitope. Results of cellular and humoral immunogenicity showed the induction of potent Thl type immune responses in rMs064 immunized mice. Taken together, the results of in vitro imrnunomodulatory effects and immunogenicity support the future evaluation of rMs064 as an experimental vaccine against TB in challenge experiments.